Estimation of Valdecoxib in Pharmaceutical Dosage Forms by Reverse Phase HPLC - Srinivas, M.S.; Srinivas, L.D.; Sastry, B.S. (Asian Journal of Chemistry, 2016)
A rapid and sensitive reverse phase high performance liquid chromatographic method has been described for the estimation of valdecoxib in bulk samples and pharmaceutical dosage forms using RP C-18 column. The mobile phase consisted of 0.01 M ammonium acetate in water and acetonitrile in the ratio 50 : 50 (v/v) and was pumped at 1.5 mL/min at 40°C. The detection was carried out at 243 nm and the calibration curve was linear in the range of 5 to 150 μg/mL. The method was statically validated for its linearity, precision and accuracy. The intra- and inter-day variation was found to be less than 1 % showing high precision of the assay method. The detection limit was found to be 5 μg/mL. Due to its simplicity, rapidness, high precision and accuracy, the proposed HPLC method may be used for determining valdecoxib in bulk drug samples or in pharmaceutical dosage forms.